2022
DOI: 10.3390/su14031631
|View full text |Cite
|
Sign up to set email alerts
|

Employee Recognition, Task Performance, and OCB: Mediated and Moderated by Pride

Abstract: Employee recognition, an incentive approach often used in management practice, plays an important role in organizations. In comparison to other incentive methods, employee recognition does not focus on the amount of money and material, but it does recognize employees and their achievements and values in the workplace. We would like to reveal the outcome and emotional mechanism of employee recognition in this work. Based on the broaden-and-build theory, we explored the role of the emotion pride on the relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…The connotations of pride in our research not only include this type of event but also contain other positive events that can help employees show their excellent ability, such as getting praise or appreciation from others ( Ohly and Schmitt, 2013 ), as well as being able to handle a challenging situation ( Tavel et al, 2022 ). All of these positive work events can trigger employees’ positive emotions because they are their moments of glory ( Yang et al, 2022 ). Moreover, connection has a positive but small direct effect (β = 0.155, p < 0.05) on PE.…”
Section: Discussionmentioning
confidence: 99%
“…The connotations of pride in our research not only include this type of event but also contain other positive events that can help employees show their excellent ability, such as getting praise or appreciation from others ( Ohly and Schmitt, 2013 ), as well as being able to handle a challenging situation ( Tavel et al, 2022 ). All of these positive work events can trigger employees’ positive emotions because they are their moments of glory ( Yang et al, 2022 ). Moreover, connection has a positive but small direct effect (β = 0.155, p < 0.05) on PE.…”
Section: Discussionmentioning
confidence: 99%
“…In such markets, primary research is often the most reliable source. The questionnaire adopted constructs on CSR from Manzoor et al (2019b) ‘s study, those on OOC from Cameron and Quinn (2011) ‘s study, while the constructs on Firm Reputation and OCB were taken from Tangngisalu et al (2020) and Yang et al (2022) ‘s studies, respectively.…”
Section: Methods Of the Studymentioning
confidence: 99%
“…Organizational citizenship behavior: In this study, we employed the OCB scale established by Yang et al (2022) , and previously used in the literature ( Bachrach et al, 2007 ). Total of 10 items using the Likert five-point scale measurement, the score was from 1 to 5, indicating “strongly disagree” to “strongly agree.”…”
Section: Methods Of the Studymentioning
confidence: 99%
“…OCB is a term used to identify behaviors carried out by employees outside of their main duties, but these behaviors are desirable and useful for the organization (Neami & Shokrkon, 2004). OCB as an outcome variable besides task performance to further enrich the gaps in relevant literature by examining how recognition practices (non-financial incentives) provided by superiors influence employees of their in-role and extra-role outcomes, which are task performance and OCB (Yang et al, 2022) 2. Reward According to Nicholas and Shadily (2015: 485), the word reward comes from the English language, which means reward or reward.…”
Section: Literature Review and Hypotheses Development A Literature Re...mentioning
confidence: 99%
“…Meanwhile, Fitriastuti's (2013) research showed that OCB has a significant positive effect on team member performance. In addition, team member recognition has a significantly positive effect on task performance and OCB (Yang et al, 2022).…”
Section: Introductionmentioning
confidence: 97%